Dietary supplements could prevent cardiometabolic syndrome: Are they safe and reliable enough for disease prevention and health promotion? - Télessy, Istvan G.; Buttar, Harpal S.; Wilson, Douglas W.; Okpala, Charles Odilichukwu R. (Frontiers in Cardiovascular Medicine, 2023)
Dietary supplements (DS) and their purchase is often based on a consumer's personal choice and advertisements. The associated DS regulations, particularly in manufacturing and marketing, are far more flexible and permissive than that of the well-regulated prescription pharmaceuticals. However, the adverse health effects associated with the inadvertent use of mega-doses of DS are not well understood. The demand for DS, nutraceuticals, and herbal remedies has experienced an upswing during the past two to three decades, and global product sales have thrived. More so, the prevention of cardiometabolic syndrome (CMS) and related disorders like diabetes mellitus, obesity, hypertension, and serum lipid abnormalities, as well as of other noncommunicable diseases (NCDs), is of highest health care priority globally, since these disorders impose very high economic burdens on health care systems and society. In this review, we argue why DS could prevent cardiometabolic syndrome, by providing the potential benefits and risks associated with them, especially self-medication considering their intake by the public at large. Good manufacturing practices and quality control are absolutely necessary for the manufacture of DS products, and proper labeling is needed regarding the optimal dose schedules of various DS and bioactive ingredients. Specific examples are used to underscore the indications and dosage recommendations made for the marketing and promotion of fish oil, coenzyme Q10, and Mg-containing products for the prevention of cardiometabolic syndrome.